Adaptasi Budaya Mahasiswa Indonesia pada Program Study of The U.S. Institutes (SUSI) 2024 di Amerika Serikat - Mubarak, Ahmad Yusuf; Saiful Akmal; Hasan Basri M Nur (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study aims to examine the communication strategies of Indonesian students in adapting during the Study of the U.S. Institutes (SUSI) 2024 program in the United States. The background of this research stems from the challenges participants face in adjusting to a multicultural environment, including language differences, social systems, and cultural expressions. Intercultural communication skills are a key factor in the success of this program. This study employs a qualitative design with a phenomenological approach to understand participants' direct experiences. Data were collected through in-depth interviews with four students who participated in SUSI at the University of Nevada, Reno, and Temple University, Philadelphia. The sample was selected using the convenience sampling method, and data analysis was conducted through reduction, presentation, and conclusion drawing. The results indicate that participants employed convergence, divergence, and over-accommodation strategies to adapt. Additionally, behavioral changes were observed after returning to Indonesia, such as cultural assimilation and integration. This study enriches the understanding of cultural adaptation in student exchange programs and serves as a reference for further research on the long-term impact of intercultural interactions on participants' identities and communication patterns. The implication of this research for future studies is the need for further exploration regarding the impact of cultural exchange programs on participants' identities and communication patterns in the long term.